2021
DOI: 10.4103/ija.ija_119_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combinations of dexamethasone-ondansetron and dexamethasone-ondansetron-aprepitant versus aprepitant alone for early postoperative nausea and vomiting after day care gynaecological laparoscopy

Abstract: Background and Aims: This study was designed to compare the effectiveness of the combination of dexamethasone–ondansetron with oral aprepitant alone and triple combination therapy with all three agents (dexamethasone-ondansetron and oral aprepitant) in the prevention of postoperative nausea and vomiting (PONV) in day care gynaecologic laparoscopy. Methods: This was a randomised clinical trial conducted at a university teaching hospital. A total of 105 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Seven studies reported the incidence of vomiting. [9,12–14,18,23,24] A significant advantage was detected in the group treated with aprepitant (OR: 0.20, 95% CI: 0.08, 0.50, P = .0005) (Fig. 3C).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Seven studies reported the incidence of vomiting. [9,12–14,18,23,24] A significant advantage was detected in the group treated with aprepitant (OR: 0.20, 95% CI: 0.08, 0.50, P = .0005) (Fig. 3C).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, pooled data from 3 studies that analyzed dexamethasone and ondansetron combined with aprepitant [14,15,18] showed that the incidence of PONV in dexamethasone and ondansetron combined with aprepitant groups was significantly lower than that of control groups given dexamethasone combined with ondansetron (OR: 0.36, 95% CI: 0.16, 0.82, P < .05) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations